High RAC3 expression levels are required for induction and maintaining of cancer cell stemness - Panelo, Laura Carolina (2017)
RAC3 is a transcription coactivator, usually overexpressed in several tumors and required to maintain the pluripotency in normal stem cells. In this work we studied the association between RAC3 overexpression on cancer cell stemness and the capacity of this protein to induce cancer stem properties in non tumoral cells. We performed in vitro and in vivo experiments using two strategies: by overexpressing RAC3 in the non tumoral cell line HEK293 and by silencing RAC3 in the human colorectal epithelial cell line HCT116 by transfection. Furthermore, we analysed public repository microarrays data from human colorectal tumors in different developmental stages. We found that RAC3 overexpression was mainly associated to CD133+ sidepopulation of colon cancer cells and also to early and advanced stages of colon cancer, involving increased expression of mesenchymal and stem markers. In turn, RAC3 silencing induced diminished tumoral properties and cancer stem cells as determined by Hoechst efflux, tumorspheres and clonogenic growth, which correlated with decreased Nanog and OCT4 expression. In non tumoral cells, RAC3 overexpression induced tumoral transformation; mesenchymal phenotype and stem markers expression. Moreover, these transformed cells generated tumors in vivo. Our results demonstrate that RAC3 is required for maintaining and induction of cancer cell stemness.